A Review: The Manifestations, Mechanisms, and Treatments of Musculoskeletal Pain in Patients With COVID-19 - Wang, Lijuan; Yang, Na; Yang, Jinfeng; Zhao, Shuwu; Su, Chen (Frontiers in Pain Research, 2022)
The outbreak of the Coronavirus Disease 2019 (COVID-19) poses a serious threat to global health. Musculoskeletal (MSK) pain condition is the most frequent symptom among COVID-19 patients besides fever and cough. But there are narrow studies that research MSK symptoms in patients with COVID-19. This review mainly aims to make an overview of the current studies about MSK symptoms in COVID-19 patients, summarize the possible mechanisms of myalgia and describe the current managements of patients with COVID-19. Except as acute respiratory manifestations, COVID-19 might also affect neurological systems, which include skeletal manifestations and muscular injury. The possible mechanisms of MSK symptoms in COVID-19 include Angiotensin-converting enzyme 2 (ACE-2) and cytokine storm. ACE-2 has been proved to be the receptor of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-COV2). Moreover, studies have showed that inflammatory cytokine could cause myalgia by inducing prostaglandin E2 (PGE2) production. And the plasma levels of IL2, IL7, IL10, IL-6, TNFα and e lymphopenia were higher in patients with COVID-19. According to these potential mechanisms of myalgia, we could mainly classify these managements into pharmacological and non-pharmacological interventions for MSK symptoms in COVID-19 patients. The various treatments of each have its own merits. However, the role of vaccine is irreplaceable in prevention of this pledge that could decrease the incidence of MSK symptoms caused by COVID-19 and reduce the severity of the symptoms in patients with COVID-19 vaccine breakthrough infections.